FORMATION AND DEVELOPMENT OF REPUBLICAN ENERGY SYSTEM - G. Avetisyan (Вестник университета)
The article deals with the problem of the formation, functioning and development of the republican model of the energy system. An attempt was made to describe the model as a tool to promote effective cooperation.